Advances in material for colorimetric and fluorescent detection of arsenic - Nishtha Khansili (Biosensors and Bioelectronics: X, 2023)
Arsenic contamination in potable water has become a growing menace globally. The established method including instrumental and laboratory-based techniques can detect arsenic in water with an accuracy of 1 ppb. Nevertheless, these methods required trained expertise, laboratory set-up and installation cost. Thus, several material-based nanosensors are reported to propose a cost-effective and facile method for detection of arsenic ions with good accuracy and stable results. Out of all reported strategies, colorimetric and fluorescent assay are the most facile and adaptable method at small scale to detect arsenic ions in water. Many real-time detection strategies of arsenic are based on biomolecule functionalized nanoparticles/nanohybrids for colorimetric and fluoroscent detection. This review highlights several eco-friendly, low cost, facile, and sensitive colorimetric and fluroscent detection strategies and their commercial/futuristic role for real time water analysis.